TINDAK PIDANA YANG DILAKUKAN OLEH WANITADALAM PERSPEKTIF PERLINDUNGA HUKUM BERDASARKAN PERATURAN MAHKAMAH AGUNG REPUBLIK INDONESIANOMOR 3 TAHUN 2017 - Napitupulu, Raffles Devit Marianto; Sahari, Alpi; Onny, Medaline (Universitas Islam Sumatera Utara, 2024)
The research conducted is normative legal research with statutory methods (statute approach), conceptual approach (conceptual approach) in adjudicating women facing the law, judges have considerations based on facts in court, exploring the values that live in society, conventions and international agreements related to gender equality that have been ratified. The concept of legal protection for women in conflict with the law does not seem to be well implemented, because in reality there are still many women in Indonesia who are in conflict with the law who find it very difficult to get access to justice. Keywords: Crime, Women, Legal Protection